The Relationship Between Stress Coping and the Performance of Health Workers at the Seba Community Health Center, Sabu Raijua Regency - Berta Rosiani Djami Rihi; Noorce C. Berek; Cathrin W.D. Geghi; Luh Putu Ruliati (PROMOTOR, 2026)
Work stress is one of the factors that influence the decline in performance of healthcare workers. Stress coping, as an adaptation mechanism to work pressure, plays a crucial role in maintaining the quality of healthcare services, particularly in remote areas such as the Seba Community Health Center in Sabu Raijua Regency. This study employed a quantitative approach with a cross-sectional design. The sample consisted of 50 healthcare workers selected by simple random sampling from a population of 101. Data were collected using a stress coping and performance questionnaire, then analyzed using the Chi-Square test with a significance level of 0.05. Most respondents used emotion-focused coping strategies (58%), while the remainder used problem-focused coping (42%). Healthcare workers' performance was generally in the fair (56%) and good (44%) categories. Statistical test results showed a significant relationship between stress coping and performance (p= 0.004). The findings indicate that healthcare workers who use problem- focused coping tend to have better performance. Active and solution-oriented coping strategies support work effectiveness amidst work pressure, compared to strategies that only focus on emotional control.